Reversible restructuring of supported Au nanoparticles during butadiene hydrogenation revealed by operando GISAXS/GIWAXS. Issue 37 (25th April 2017) - James Martin, David; Decarolis, Donato; Odarchenko, Yaroslav I.; Herbert, Jennifer J.; Arnold, Thomas; Rawle, Jonathan; Nicklin, Chris; Boyen, Hans-Gerd; Beale, Andrew M.
Abstract : Supported Au NPs on Si substrates were found to reversibly change size and shape during hydrogenation of C4 H6 as studied by GISAXS/GIWAXS. Abstract : Periodically arranged, monodisperse gold nanoparticles supported on flat silicon substrates were studied for the hydrogenation of 1, 3-butadiene under operando conditions using Grazing Incidence Small- and Wide-Angle X-ray Scattering (GISAXS/GIWAXS). It was found that the composition and shape of the nanoparticles depends very much on the chemical environment; the particles are shown to be dynamic, undergoing reversible size and shape change particularly during catalytic reaction, highlighting a dynamism often not observed in traditional studies. Specifically, the size of the Au nanoparticles increases during butadiene hydrogenation and this is attributed to the partial removal of a Au2 O3 at the metal–oxide interface and consequential shape change of the nanoparticle from a more hemispherical particle to a particle with a larger height to width ratio.